A interação haitiana em Concórdia/SC - Ribeiro, Vivian Stefany (2018)
The present work was developed from the presence of Haitian immigrants in Brazil, in the western region of SantaCatarina and specifically in Concordia/SC. It intends toin estigate the social relations existing between the Groupof foreigners and Brazilians,M apping existing powerrelations and identifying relations with the city and work. Aswel as identifying the main motivations to choose the city ofConcordia/SC to work and lie. In this scenario, we opted fora qualitative methodology with interviews and informalre ports. In this research we found that the history of SantaCatarina corroborated to the construction of an imaginaryand a discourse that is present nowadays. Theserelation ships constructed from these assumptions havedelimited spaces to be occupied by bl acks and whites in thestate. This was the use of Whitetrash power mechanisms inord er to perpetuate their position of privileges and proviso.In this context, Haitian immigr ants are greeted with stigmataand stereotypes created to preserve the positions ofpri vilege between whites and non-whites.